Комбинированное лазерно-микроплазменное нанесение керамических покрытий на стали - Хаскин, В.Ю. (Видавничий дім "Академперіодика" НАН України, 2007)
A possibility for the ceramic coating deposition using the laser-microplasma technique without the preliminary abrasive jet machining of the part surface is demonstrated. The coverings obtained have high cohesive resistance and are the chemical compounds of a deposited material with iron. These coverings have high resistance to dynamic loads and sufficient thermostability.